The Role of Managerial Strategy in Innovation, Ambidexterity, Technology, and Technopreneurial Success. - Wahyudin Yahya; M.Yusuf.K; Muchriana Muchran (www.amertainstitute.com, 2025)
This study aims to evaluate the role of managerial strategy, innovation, ambidextrous organizations, and technology adoption in driving the success of technopreneurs in the digital economy era. The focus of this research is to examine how these four factors collectively enhance the performance and competitiveness of technology-based businesses amid increasingly complex digital challenges. A quantitative approach was employed, with surveys serving as the primary data collection method. The research sample consisted of 50 active technopreneurs. Prior to the distribution of questionnaires, validity and reliability tests were conducted to ensure the appropriateness of the instrument. The validity test results indicated that all questionnaire items were valid, as shown by correlation coefficients exceeding the critical value. Meanwhile, the reliability test demonstrated a high level of consistency, with a score of 0.784. The data were analyzed statistically using descriptive and inferential analysis. The Shapiro-Wilk normality test showed that the data were normally distributed with significance levels above 0.05. Further analysis using a one-sample t-test revealed that the average responses from the 50 technopreneurs were significantly higher than the benchmark score of 70, with a p-value of 0.0001. These findings indicate that managerial strategy, innovation, ambidextrous organizations, and technology adoption significantly contribute to technopreneurial success in the digital era, with advanced technology adoption being the most influential factor. The integration of these four elements forms a critical foundation for strengthening competitiveness and ensuring the sustainability of technopreneurial ventures